Ecuador - Creating Fiscal Space for Poverty Reduction : A Fiscal Management and Public Expenditure Review, Volume 2. Background Papers - World Bank (Washington, DC, 2013)
The report, a joint effort by the Bank, and the Inter-American Development Bank, seeks to provide the Ecuadorian authorities with a comprehensive account of both institutions' diagnoses and recommendations in the area of fiscal management and public expenditure. This report consists of two volumes. Volume I examines whether, and how, the core goals of public expenditure management, i.e., balanced fiscal aggregates, resource allocations to strategic sectors, and equity and microeconomic efficiency of public spending are met in Ecuador. Volume II presents sector studies on fiscal sustainability, the fiscal rules, education, health, pensions, water and sanitation, electricity, telecommunications, and oil, including the results of a national teachers tracking survey, as it concerns the education sector. It focuses on the main themes that are critical to Ecuador's fiscal consolidation and poverty reduction following dollarization. In most cases, it does provide choices for key policy questions, and, provides an independent analysis of the selected areas where both Banks are specifically involved, and a set of possible recommendations to address them. Volume I, in particular, correctly identifies fiscal vulnerabilities in the new context of dollarization, and proposes an adequate fiscal management that increases expenditure flexibility, develops budget management reform, increases public (social) investment, and brings transparency to public expenditure. All this is supported by an implicit proposal for a Fiscal Pact for Poverty Reduction. For its part, Volume II deals with sectoral policies and their link to fiscal management. It identifies the most efficient and cost-effective interventions in the social sectors, while making an optimal use of the reduced and available fiscal space. The study also recognizes the importance of political constraints, and the difficulties of setting steady rules in a non-cooperative game among national political actors that are particularly reflected in budget allocations. It correctly emphasizes the need to bring full transparency of information on the management of public accounts among all domestic actors, as a starting point for sectoral reform. The study should contribute to align fiscal and institutional policies in the social and basic infrastructure sectors, and to strengthen them in the context of the ongoing negotiations for a Free Trade Agreement with the United States, while preserving difficult domestic equilibria on the development agenda.